1986
DOI: 10.1007/bf01263211
|View full text |Cite
|
Sign up to set email alerts
|

Reoperationen nach der Fundoplicatio nach Nissen

Abstract: The main causes of unsatisfactory results after Nissen fundoplication can usually be explained by tactical and technical mistakes. The fixation of the stomach to the diaphragm is one case of the development of pain syndrome, telescopic phenomenon and relative or complete dispersion of fundoplication with subsequent development of a recurrent reflux oesophagitis. The fundoplication should be done only in hospitals which have experience in oesophageal and gastric surgery. The collar of fundoplication should be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Because of the long-term side effects of the Angelchik device as a foreign body [22], however, we generally no longer recommend it even though no complications occurred in these 2 cases up to now. Reported 30-day hospital mortality is between 0 and 17.6% [2,3,[5][6][7][8]; in our series, mortality was 2.0% (1/50). In a study of 61 patients undergoing repeated antireflux procedures after various primary procedures, Little and coworkers [6] found that mortality and morbidity increase when the number of prior operations increases.…”
Section: Discussionsupporting
confidence: 37%
See 1 more Smart Citation
“…Because of the long-term side effects of the Angelchik device as a foreign body [22], however, we generally no longer recommend it even though no complications occurred in these 2 cases up to now. Reported 30-day hospital mortality is between 0 and 17.6% [2,3,[5][6][7][8]; in our series, mortality was 2.0% (1/50). In a study of 61 patients undergoing repeated antireflux procedures after various primary procedures, Little and coworkers [6] found that mortality and morbidity increase when the number of prior operations increases.…”
Section: Discussionsupporting
confidence: 37%
“…Despite the frequent use of the Nissen fundoplication [1] as an antireflux procedure, relatively few publications have dealt with patients requiring reoperation following failed fundoplication [2][3][4][5][6][7][8][9][10]. The aim of this report is to review our experience with 50 patients reoperated for failed fundoplication of a total of 86 reoperations for failed antireflux procedures.…”
mentioning
confidence: 99%
“…The incidence of pathological stages of the artifi cial esophagus after different replacement surgeries varies in a wide range and constitutes 23-26% [6].…”
mentioning
confidence: 99%